Search This Blog

Loading...

Picture Problem Riddle

Picture Problem Riddle - 20 January






Solve this picture riddle












For Solution : Click Here

26 comments:

  1. Replies
    1. my answer is 4
      because
      7-4+3*0+1=
      3*0=0;
      7-4=3;so..............
      (7-4)+(3*0)+1
      =3+1
      =4

      Delete
  2. 7-4+3*0+1 i.e. (3+3*0+1) =(6*0+1)=(0+1)=1 is the answer

    ReplyDelete
  3. (7-4)+(3x0)+1
    3+0+1= 4

    4 is the answer
    jackson

    ReplyDelete
  4. 2. there are no brackets or parentherer so you have to do multiplication first, then division, then addition, and lastly, subtraction.

    ReplyDelete
  5. the answer is 1. You only use BEDMAS if the numbers are in brackets.

    ReplyDelete
  6. If we are using BODMAS, which is what most of us are using, then it is correct to multiply first.
    3x0=0.
    However everyone who is getting the answer 4 is doing subtraction next (7-4) when addition comes before subtraction. I claim the next step is actually
    4+0+1=5
    Finally...
    7-5=2

    ReplyDelete
    Replies
    1. With addition and subtraction you don't do one first, you go left to right. 7-4 is the same as 7+ -4. The priority is simply in order.

      Delete
  7. my answer was one then i changed it to four

    ReplyDelete
  8. I thing you should remember DMAS (Division,Multiplication,addition, subtraction).

    here there is no division.so first is Multiplication.
    so 3*0 = 0
    now the expression is =7- 4 + 0 +1
    now = 7 - 4 +1
    than addition takes place
    so the expression is = 8 - 4
    so =4
    And finally 7-4+3*0+1 = 4

    ReplyDelete
    Replies
    1. But you add first before subtracting so the answer is 2

      Delete
    2. What you said is absolutely correct.. Thank you

      Delete
    3. What you said is absolutely correct.. Thank you

      Delete
    4. What you said is absolutely correct.. Thank you

      Delete
  9. Using the BODMAS rule:
    for the LHS
    we will first add then subtract
    i.e., 7-(4+3)
    7-7=0
    then lets go to the RHS.
    0 + 1 = 1
    Therefore we combine all and come to the equation that 0x1
    that is 0x1 = 0
    because any number multiplied by zero equals zero..
    Hope that answers your question..
    Thank you..

    ReplyDelete
  10. 7-4 + 3*0 + 1 =?
    (7-4) + (3*0) + 1 =?
    7-4 =3
    3*0 =0
    3+0+1 =4
    Sorry if it's confusing

    ReplyDelete